2020
DOI: 10.1002/cncr.33352
|View full text |Cite
|
Sign up to set email alerts
|

Examining the dynamic nature of nonverbal communication between Black patients with cancer and their oncologists

Abstract: Background Although communication quality is associated with patient outcomes, racial disparities in communication exist, disproportionately burdening Black patients. However, most communication research focuses on verbal behaviors in predominantly White patient populations. We used a newly developed and theory‐guided network analysis that examines the dynamic interplay and behavioral convergence and divergence between Black patients with cancer and their oncologists during cancer treatment discussions. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…In a further explorative step, the temporal associations across coaching sessions were modeled, using a network approach (Epskamp, 2020 ; Jordan et al, 2020 ), which has recently been applied to various fields of psychology, such as clinical psychology (Lutz et al, 2018 ; Kaiser and Laireiter, 2019 ) or patient-physician interactions (Hamel et al, 2020 ). In this modeling approach, a phenomenon is seen as a network of specific elements (e.g., symptoms, factors) that dynamically interact and impact one another over time.…”
Section: Methodsmentioning
confidence: 99%
“…In a further explorative step, the temporal associations across coaching sessions were modeled, using a network approach (Epskamp, 2020 ; Jordan et al, 2020 ), which has recently been applied to various fields of psychology, such as clinical psychology (Lutz et al, 2018 ; Kaiser and Laireiter, 2019 ) or patient-physician interactions (Hamel et al, 2020 ). In this modeling approach, a phenomenon is seen as a network of specific elements (e.g., symptoms, factors) that dynamically interact and impact one another over time.…”
Section: Methodsmentioning
confidence: 99%
“… 27 Our study team recently observed that in an oncology setting, patients and oncologists smile, orient themselves to 1 another, and lean in toward 1 another at similar rates of frequency, but oncologists are more likely than patients to display an open posture. 21 Oncologists tend to interrupt patients more than patients interrupt oncologists, and oncologists spend more time speaking compared to patients. We also see that patients exhibit continuer behaviors (eg, head nods) to a greater extent than oncologists.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining racial disparities in communication, the results found that communication quality was improved when physicians’ behavior was matched to that of the patients. For example, physicians could focus on matching patient behaviors of smiling, gazing, and laughter as these behaviors have been shown to elicit a favorable response from patients ( Hamel et al, 2021 ). Studies have also shown that the implicit racial bias of physicians can be decreased significantly by completing the Black-White IAT during the first and last semester of medical school ( van Ryn et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities in communication have been documented and are considered driving factors for poor treatment adherence and negative experiences in the health care setting ( Hamel et al, 2021 ). When recordings of clinic visits were assessed by independent raters, non-White patients were found to experience unfavorable treatment and suboptimal communication compared to their White counterparts.…”
Section: The Clinical Encountermentioning
confidence: 99%